Identifikasi Faktor-Faktor Yang Mempengaruhi Keterlambatan Proyek Infrastruktur Kereta Cepat Jakarta-Bandung - Yurianto Yurianto; Trihono Kadri (Universitas Trisakti, 2020)
High speed trains are designed with a speed of more than 350 km/ hour. High speed trains in Indonesia were built by PT Kereta Cepat Indonesia China (KCIC). The route served from Halim station in Jakarta to Tegal Luar Sation, which is located in Bandung district, has a length of 142.3 km. The construction of the fast train is divided into 4 (four) sections including sections 1, 2, 3 and 4. This fast train line consists of an elevated, tunnel and subgrade. Some construction works often experience delays due to complexity, land availability, design delays and availability of resources. Implementation time is an important factor in project management besides cost and quality. There are several factors that hinder the completion of the Jakarta-Bandung fast train project, so it is necessary to conduct a study on the inhibiting factors and solutions to minimize delays. The research method used is AHP weighting analysis. Based on the analysis and discussion, it can be concluded that from 61 potential aspects of the cause of the delay, there are 11 variables that affect the implementationtime of the Jakarta-Bandung fast train infrastructure development project based on the AHP ranking, including constraints in land acquisition for infrastructure buildings (63,144%), scheduling very strict projects by owners (61,771%), work order plans that are not well structured / integrated (61,570%), unavailability (materials, tools, labor) as needed (57,216%), shop drawings are not ready on time, no opportunity to learn (56,266%), changes in design / work details during implementation (56,170%), quite complicated project coordination (54,851%), negligence / delay by work sub contractors (53,081%), unclear technical specifications and less firm because it is too general (52,837%), there is a development permit procedure that is dip ery difficult for various parties (50,370%) and unfavorable weather conditions (49,680%)